The shared signaling pathways of autism-risk genes and their disruption by genetic variants - Murtaza, Nadeem (My University, 2022)
Autism spectrum disorder (ASD) encompasses a broad range of neurodevelopmental disorders, with two core symptoms: deficits in social communication, and restrictive interests and repetitive behaviors. Genetics is thought to play a large role in ASD and currently there are hundreds of associated genes. We first studied the thousand and one amino acid kinase gene (TAOK2), which plays an important role in neurodevelopment. We found that loss of TAOK2 causes deficits in neuron development and activity, leading to morphological changes in various mouse brain regions and ASD-related behaviors. We studied the impact of de novo mutations identified in TAOK2, which caused aberrant neuron dendritic arborization and formation of synapses. To elucidate how TAOK2 regulates neuron development we used a proximity-labeling proteomics technique (BioID) to identify its protein-protein interaction (PPI) network. We applied this same methodology to a total of 41 ASD-risk genes and observed multiple convergent biological processes, including the less-studied mitochondrial and metabolic pathways. ASD-risk genes, including TAOK2, associated with mitochondrial proteins were found to have altered cellular respiration. The shared ASD-risk gene PPI network enriched for other ASD-risk genes and was used to group genes based on their shared PPI networks. These gene groups showed correlation between the clinical behavior scores of individuals that had mutations within the distinct gene groups. Lastly, we identified changes in the PPI networks of multiple ASD-risk genes through BioID, which we validated with various functional assays. In summary, we developed a proximity-labeling proteomics method that identified multiple convergent biological pathways associated with ASD. Studying the function of TAOK2 revealed multiple disease-relevant pathologies associated with the disorder, however proximity labeling has the potential to categorize multiple ASD-risk genes and elucidate their shared signaling pathways, which together, can advance the development of robust treatments for ASD.
INVESTIGATING THE CONVERGENT DISEASE-RELEVANT MECHANISMS IN AUTISM SPECTRUM DISORDER
Keywords: Neurodevelopmental Disorder; BioID; Autism spectrum disorder